Coordination and variability of muscular activation in male athletes with and without subacromial impingement syndrome: A case-control study - Sheikhhoseini, R.; Abdollahi, S.; Salsali, M.; Anbarian, M.; Guess, T.M. (PLOS ONE, 2025)
Objectives Athletes with Subacromial Impingement Syndrome (SIS) exhibit altered muscular coordination and variability during repetitive shoulder movements compared to athletes without SIS. This research compared the Coordination and Variability of Muscular Activation in Male Athletes with and Without SIS.